Aligning cloud computing security with business strategy - Mohamed Hassan El-Hoby, Hany; A. F. Salah, Mohammed; Suhaimi, Mohd Adam (Seventh Sense Research Group, 2014)
These days, the technological growth in the IT sector is rapid. Cloud computing is also one of the new technologies that have both benefits and limitations. This paper gives an overview of how cloud computing can be helpful for an enterprise. It emphasizes on how cloud computing can be adopted in the IT sector. The paper also discusses the security issues of cloud computing. This article also highlights the issue of data leakage in this technology which faces cloud computing clients. The authors have designed a model to solve this issue through data isolation. A business value will be achieved through the proposed model by aligning the cloud computing security with the business strategy and increase the security procedures to verify the authenticated users through the virtual system.